Predictive Factors of Drug Addiction among Women in Golestan Province - Alireza Ghorbani; Akram Mohammadi-Nikou (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Women are potentially exposed to drug addiction in the community as half of the country's population and over the past years the extent of drug-related harm has spread to the population of women. The study aimed to identify predictors of addiction among women in Golestan province in northern Iran. Materials and Methods: The study was of descriptive-analytical design. The statistical population consisted of female addicts who were referred to private drug addiction centers in Gorgan and Azad-Shahr in Golestan Province, among whom 150 were selected by simple random sampling. Data were collected via of sociodemographic characteristics of substance abuse questionnaire. Data analysis was performed using descriptive statistics including statistical, mean, standard deviation and inferential statistics including multivariate regression analysis using SPSS-18 software. Results: The mean (SD) age of participants was 33.7 (4.2) and onset age of substance abuse 21.8 (6.9). As many as 61 (40.7%) of participants had primary school education, 73 (48.7%) were married, 41 (27.3%) reported a history of substance abuse by their fathers, and 72 (48%) mentioned opium as the most abused substance. Family factors (P<0.01), social factors (P<0.05) and age (P<0.01) were the strongest predictors of drug addiction among women. Psychosocial and psychological factors, education, marital status and economic status failed to predict drug addiction in women. Conclusion: The study showed that increased age, social scores, and scores of family factors were associated with increased drug addiction among women. In this study, marital status and economic factors including the occupational status and economic status did not predict the women's addiction.   DOI: http://doi.org/10.22037/ch.v6i2.21920